Effect of palm-based soap noodles dust concentration on dust explosion severity in a spherical vessel - Muhammad Syahrul Ridhzuan, Mazilan; Siti Zubaidah, Sulaiman; Azizul Helmi, Sofian; Siti Kholijah, Abdul Mudalip; Rohaida, Che Man; Zatul Iffah, Mohd Arshad; Shalyda, Md Shaarani @ Md Nawi (Elsevier Ltd, 2023)
The dust explosion propagation of palm-based soap noodles was experimentally studied in a 20-L spherical vessel. Understanding the effect of concentration on this metric is a prerequisite to characterizing the severity of the explosion. This study focused on the link between concentration and overpressure (Pmax), rate of pressure rise (dP/dt), and deflagration index (KST). The highest Pmax, dP/dt, and KST were recorded at 400 g/m3, corresponding to a class St-2 dust with a strong explosion. The agglomeration process evidently controlled the mass burning rate, which affected the dust explosion propagation. This data can help design preventive measures related to palm-based soap noodle dust explosions.